Jeff Aaron
Odd that you used a small y for "y intercept" but a capital y in the equations. You should be consistent.
Y = 2x^2 + 4x - 3
Complete the square:
Y = 2(x^2 + 2x) - 3
Y = 2(x^2 + 2x + 1 - 1) - 3
Y = 2(x^2 + 2x + 1) - 2 - 3
Y = 2(x + 1)^2 - 5
The vertex is where the part in brackets is zero: x + 1 = 0, so x = -1, and Y = 2*0^2 - 5 = -5
At the y intercept, x = 0, so Y = -3
Y = 4x^2 - 8x + 9
Complete the square:
Y = 4(x^2 - 2x) + 9
Y = 4(x^2 - 2x + 1 - 1) + 9
Y = 4(x^2 - 2x + 1) - 4 + 9
Y = 4(x - 1)^2 + 5
The vertex is where the part in brackets is zero: x - 1 = 0, so x = 1, and Y = 4*0^2 + 5 = 5
At the y intercept, x = 0, so Y = 9
Philip
1) y = 2x^2 + 4x - 3 = 2x^2 + 4x + 2 - 5 = 2(x+1)^2 - 5. Vertex is @ (-1,-5). y-intercept occurs when x
= 0. y(0) = - 3. y-intercept s @ (0,-3).
2) y = 4x^2 - 8x + 9 = 4x^2 - 8x + 4 + 5 = 4(x - 1)^2 + 5. Vertex is @ (1,5). y-intercept is @ (0,9).
Matthew
I'm really confused. Please explain aswell